Views and preferences of parents, teachers and principals on the implementation of the language policy in primary schools in Namibia (Journal for Studies in Humanities and Social Sciences, 2014)
The language policy of schools in Namibia states that from grade 1 to grade 3, learners should receive education in their mother tongues. The mother tongue becomes a subject from grade 4 onwards while English takes over as the medium of instruction. This paper presents the views of parents, teachers and principals and parents on how this policy is implemented in three schools studied in the Khomas region. Data were collected using semi-structured interviews from one urban school, one peri-urban school and one rural school. The fi ndings of the study refl ect diff erent language preferences between parents and teachers, the latter favouring English and the former advocating the mother tongue as